Crisis communication and organizational learning in Finnish public sector organizations during Covid-19 - Pihamaa, Maria (2025)
This master's thesis explores organizational learning in the contexts of crisis communication and crisis management. Although crises can inflict many challenges upon public organizations, they can also be viewed as learning opportunities. As organizations are highly likely to face crises and as crises are becoming more varied, investigating this topic can help to understand what types of learning crises lead to, how organizations respond to challenges during a crisis, and whether learning resulting from a crisis is long-term or short-term. This thesis employs qualitative thematic analysis to explore changes in crisis communication strategies and organizational learning in Finnish public sector organizations during the Covid-19 pandemic. Data was collected using semi-structured interviews, and six communications professionals working in public sector organizations during the pandemic were interviewed. The findings indicate that organizations made significant changes to their crisis communication during this time, and organizational learning could be detected. The results show that organizations increased their focus on making their communication understandable and adapted their communication channels. The pandemic also resulted in value changes in organizations. It changed how communication and crisis communication are perceived and how organizations view their preparedness towards crises. Additionally, multiple supporting and hindering factors for effective crisis communication could be recognized. Results of this thesis indicate that crises can present learning opportunities, which, when addressed properly, could lead to organizational learning and increase crisis preparedness. This thesis combines theories of crisis communication and organizational learning to create a comprehensive view of the phenomenon. The findings indicate potential practical implications in the need to increase the focus on crisis communication in organizations in order to increase crisis preparedness.